Research Programmes that Address Societal Challenges — Aligning Policy, Implementation, and Expected Impact - Irene Ek (Foresight and STI Governance, 2018)
This article explores research programs that address societal challenges. In recent years, the rationale for innovation policy has been extended to include support instruments more explicitly designed to address societal challenges. While there are broad agreements that in this rationale research and innovation support can not only stimulate growth and economic activity, but it can also actively be directed towards meeting societal challenges. However, exploring how societal challenge policy goals can be translated into something that the support instruments can influence, are not yet the focus of challenge-driven innovation policy and a topic that seems to be neglected in the research literature. This article develops a framework for a cross country analysis of how policy, programs, and impact align and highlight what can be learned from selected societal challenge programs.